STUDY OF HYDROTHERMAL ALTERATION, VEIN CHARACTERISTICS, AND FLUID INCLUSIONS DEEP MILL LEVEL ZONE (DMLZ) AREA, INTAKE AND EXHAUST LEVEL, ERTSBERG DISTRICT. PAPUA PROVINCE - Hertanto, Tito
Research area is located in Deep Mill Level Zone (DMLZ), Ertsberg District, Mimika Regency, Papua Province. Deep Mill Level Zone is an underground mine with the porphyry–skarn deposit that is located in mine area of PT Freeport Indonesia. This study was conducted to determine the geological setting, hydrothermal alteration, vein characteristics and its distribution, and hydrothermal fluid characteristics. The method used is geological and alteration mapping, description of four drill holes, petrographic analysis of 35 samples, mineragraphic analysis of five samples, and fluid inclusions analysis (petrographic–microthermometry) of two samples. The study area is composed of six rock units, from old to young, namely Quarzite Unit, Hornfels Unit, Marble Unit, Quartz Monzodiorite Unit, Porphyry– Monzogranite Unit, and Porphyry–Rhyolite Unit. Geological structure of the study area is NW-SE and NE-SW strike–slip minor faults. Hydrothermal alteration zone is divided into six zones, i.e. Diopside–Garnet–Epidote Zone (exoskarn), Biotite–Feldspar–Quartz Zone (potassic), Chlorite–Epidote±Actinolite Zone (propylitic), Diopside–Garnet±Epidote Zone (endoskarn), Sericite– Carbonate±Pyrophyllite Zone (phyllic), and Anhydrite–Carbonate Zone (exoskarn). Vein types of the study area is composed of M–type (magnetite vein), A–type (quartz – chalcopyrite ± magnetite ± pyrite ± biotite vein), B–type (quartz – chalcopyrite ± molybdenite ± pyrite vein), and D–type (quartz– pyrite±chalcopyrite vein with sericite halo). Fluid inclusions analysis result of B– type vein contains fluid inclusion with homogenization temperature 447.3– 541.90C and salinity 9.7–17.4 wt.% NaCl equivalent, while D–type vein contains fluid inclusion with homogenization temperature 310.8–424.20C and salinity 3.4– 7.2 wt.% NaCl equivalent. Hydothermal alteration of the study area is divided into three stages, i.e. isochemical metamorphism, progradation metasomatism, and late retrogradation stage. The distribution of alteration mineral is controlled by structures and host rocks. Relationship between homogenization temperature and salinity of B–type and D–type vein showed the depression pattern, caused by mixing cold meteoric water.